Faktor-Faktor yang Memengaruhi Harga Bawang Merah di Indonesia - Anggorojati, Raden Roro Siti Binar; Badriah, Lilis Siti; Priyono, Rakhmat (Lingka Ekonomika, 2022)
The purpose of this research is to (1) analyze the effect of shallot consumption, shallot production, chili prices, and the exchange rate in shallot prices in Indonesia, (2) to analyze the most influential variables in shallot prices in Indonesia in 1999-2019. This research is a quantitative descriptive study with secondary data for a period of 21 years, 1999-2019. The data analysis technique used is multiple linear regression analysis, and elasticity test. Based on the results of the study, (1) the results of multiple linear regression of chili production and price variables had a significant positive effect on the price of shallots in Indonesia in 1999-2019. Meanwhile, the shallot consumption variable and the exchange rate have no significant effect on the price of shallots in Indonesia in 1999-2019. (2) The value of chili is the most influential variable in the price of shallots in Indonesia in 1999-2019. The implication of this research is that the government is expected to be able to maintain the stability of the price of shallots and chili prices so that the prices of shallots and chilies in the country are more stable. In addition, the government is expected to improve the performance of post-harvest technology, more efficient cultivation technology or the shallot processing industry and government policies in an effort to protect producers.